2021
DOI: 10.1007/s11060-021-03806-7
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing stereotactic radiosurgery in patients with recurrent or residual craniopharyngiomas

Abstract: Stereotactic radiosurgery (SRS) is an important management strategy for residual and recurrentCraniopharyngiomas. The current study evaluated the factors which affected tumor control and complications in craniopharyngioma SRS. MethodsThis study includes 53 consecutive patients who underwent single-session SRS for recurrent or residual craniopharyngiomas. The median age was 41 years with 28 male and 25 females. The median tumor volume was 0.63 cm 3 and median margin dose was 12 Gy (range, 9-25 Gy). ResultsThe o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…In that study, almost half of the patients had a tumor recurrence, resulting in treatment failure during the long-term period due to the reduced marginal dose of ≤10 Gy when the tumors adhered to the optic apparatus. Similar outcomes were reported in other studies in which higher margin dose (≥12 Gy) enables better local tumor control,[ 20 ] but sufficient distance to the optic nerve (≥2 mm, ≥3 mm or 3–5 mm)[ 6 , 7 , 19 , 20 ] is necessary to achieve that.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…In that study, almost half of the patients had a tumor recurrence, resulting in treatment failure during the long-term period due to the reduced marginal dose of ≤10 Gy when the tumors adhered to the optic apparatus. Similar outcomes were reported in other studies in which higher margin dose (≥12 Gy) enables better local tumor control,[ 20 ] but sufficient distance to the optic nerve (≥2 mm, ≥3 mm or 3–5 mm)[ 6 , 7 , 19 , 20 ] is necessary to achieve that.…”
Section: Discussionsupporting
confidence: 84%
“…GKS has been reported to be an effective management option and studies have suggested 5-year progression-free survival rate of 72.1–90.3%. [ 4 , 16 , 20 , 26 ] However, these studies focused on one treatment and the comparison of outcomes from other radiation strategies and criteria for selecting treatment plans have not been established. GKS was mainly performed in a single fraction and it can threaten visual function when the tumor was touching or compressing the optic nerve.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Larger case series with long-term follow-up in patients undergoing stereotactic radiosurgery for previously operated tumors have demonstrated tumor control rates of between 60.8-76% at 5 years and 42.6-60.2% at 10 years [81][82][83][84][85][86][87]. However, radiation dosing must be carefully planned as adequate doses greater than 12 Gy have been shown to yield better local control [88] but maximum dosing exceeding 35 Gy may lead to tissue toxicity [85]. Adverse radiation rates in larger case series have ranged from 6.2-10.9%, most commonly hypopituitarism, followed by visual deficits and hypothalamic obesity [83,86].…”
Section: Radiationmentioning
confidence: 99%